Linha Morgan e sua relação com a displasia coxofemoral em cães - Fernanda Guimaraes Miranda (2013)
It has been evaluated 160 (four of each dog) hip joints radiographs of 40 different breeds of dogs (25 females and 15 males) from the metropolitan area of Belo Horizonte, Minas Gerais, Brazil.The radiographs of each animal were obtained at two different stages: stage 1 (mean 7.23 months) and stage 2 (mean 14.25 months). The conventional radiographic method (CRM) and the radiographic distraction method (RDM) were used, carried out in both stages. In CRM, the relationship between the femoral head and acetabulum through the Norberg angle (NA) was quantificated. The angle of inclination (AI) was measured and the presence of degenerative joint disease (DJD) had been evaluated. The RDM was performed to establish the distraction index (DI). The objectives were to evaluate the presence of the Morgan line and other signs of DJD and correlated them with the degree of canine hip dysplasia (CHD) and also check if the DI greater than 0.3 (first stage) was associated with the presence of ML (second stage). It was found that age, DI, AI, changes of femoral neck and the formation of osteophytes were associated with the presence of ML.It was observed that if the DI is greater than 0.3 at the first stage, the chance of a positive outcome of ML in the second stage increases by 7.2 times. Thus, 49 joints showed ID > 0.3 at the first stage, in which 31(63.3 %) presented ML at the second stage. 31 animals showed ID <or = 0.3 at first, and only six (19.4%) had LM at the second stage. There has been a significant association between the presence of ML and the degree for CHD. The more severe the CHD, the higher the percentage of positive ML results.Thus, among the 24 (60 %) animals that showed ML, 11 (45.83 %) were classified as severe dysplastics, 5 (20.83%) as moderate and 8 (33.33 %) as mild. None of the animals classified as normal or near dysplastics presented ML. Among the 8 animals classified as mild dysplastics, 5 showed only ML as DJD.